Using technology to encourage student engagement with feedback: a literature review - Brian Irwin; Graham Holden; Stuart Hepplestone; Louise Thorpe; Helen J. Parkin (Association for Learning Technology, 2011)
This article presents a review of the literature over the past 10 years into the use of technological interventions that tutors might use to encourage students to engage with and action the feedback that they receive on their assessment tasks. The authors hypothesise that technology has the potential to enhance student engagement with feedback. During the literature review, a particular emphasis was placed on investigating how students might better use feedback when it is published online. This includes where an adaptive release technique is applied requiring students to submit an action plan based on their feedback to activate the release of their grade, and electronic generation of feedback using statement banks. Key journals were identified and a snowball technique was used to select relevant literature. The use of technology to support and enhance student learning and assessment is well documented in the literature, and effective feedback practices are similarly well published. However, in terms of the use of technology to support and enhance feedback processes and practices (i.e. production, publication, delivery and students making use of feedback through technology), we found the literature to be limited.